Trend Analysis of Flipped-Classroom Research in English as A Foreign Language - Agus Hidayat; Septa Aryanika; Mohammad Ridho Kholid; Rohmatillah Rohmatillah; Nur Syamsiah; Nunun Indrasari; Dian Reftyawati (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
The researchers accessed the online Scopus database to gather data for the study. The researchers utilized Microsoft Excel for frequency analysis, VOSviewer for data visualization, and Harzing's Publish or Perish for citation metrics and analysis. According to a keywords search for "Flipped-Classroom” and “EFL," 26 articles were assessed. The research on this matter was started in 2014 with one article for the entire year. From the next year to 2020, the number of publications each year grew. As a result of analysis, the researcher discloses the data on the growth of the research, the most active journals on the topic, the distribution of author keywords and co-occurrences of author keywords, and the most active authors and authors’ collaboration. It was shown that throughout the last seven years, researchers have increased their focus on flipped classroom and EFL research, with the highest number of publications occurring in 2020 (11 papers). The most active journal on the subject is the International Journal of Emerging Technologies in Learning, which has published three pieces on the subject. Additionally, the investigation found that instruction, perception, and performance are the most commonly used keywords. However, involvement and motivation are mentioned infrequently in research reports.